2024
DOI: 10.21203/rs.3.rs-3818580/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-COVID cognitive deficits at one year are global and associated with elevated brain injury markers and grey matter volume reduction: national prospective study

Benedict Michael,
Greta Wood,
Brendan Sargent
et al.

Abstract: The spectrum, pathophysiology, and recovery trajectory of persistent post-COVID-19 cognitive deficits are unknown, limiting our ability to develop prevention and treatment strategies. We report the one-year cognitive, serum biomarker, and neuroimaging findings from a prospective, national longitudinal study of cognition in 351 COVID-19 patients who had required hospitalisation, compared to 2,927 normative matched controls. Cognitive deficits were global and associated with elevated brain injury markers and red… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Most of the research that has identified manifest cognitive deficits typically involves more severe respiratory cases of COVID-19 [50][51][52] or those who present neurological symptoms during the acute episode. 9 Additionally, these patterns of results are more likely to be found when focusing on a subset of the population that likely represents a more susceptible group, such as those individuals who report subjective cognitive symptoms persisting for more than a month after infection. 9 A study using web-based assessments over a large sample of subjects found that individuals recovering from COVID-19 exhibited alterations in cognitive tests, with more pronounced effects observed in those who were hospitalized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the research that has identified manifest cognitive deficits typically involves more severe respiratory cases of COVID-19 [50][51][52] or those who present neurological symptoms during the acute episode. 9 Additionally, these patterns of results are more likely to be found when focusing on a subset of the population that likely represents a more susceptible group, such as those individuals who report subjective cognitive symptoms persisting for more than a month after infection. 9 A study using web-based assessments over a large sample of subjects found that individuals recovering from COVID-19 exhibited alterations in cognitive tests, with more pronounced effects observed in those who were hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, these patterns of results are more likely to be found when focusing on a subset of the population that likely represents a more susceptible group, such as those individuals who report subjective cognitive symptoms persisting for more than a month after infection. 9 A study using web-based assessments over a large sample of subjects found that individuals recovering from COVID-19 exhibited alterations in cognitive tests, with more pronounced effects observed in those who were hospitalized. 53 However, significant alterations were also evident in those who did not require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] One study found the cognitive deficits associated with long COVID in those hospitalized for COVID-19 were equivalent in magnitude to 20 years of aging. [27] It is estimated that close to 1 in 4 American adults who currently have long COVID have significant activity limitations. [22] COVID-19 Burden vs.…”
Section: Figurementioning
confidence: 99%